Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.0039
|View full text |Cite
|
Sign up to set email alerts
|

Charge-sign dependent modulation of cosmic ray electrons and positrons up to extreme solar maximum conditions

Abstract: The charge-sign dependent modulation of cosmic rays is an important topic in solar modulation studies, providing insights into gradient, curvature, and current sheet drifts. Such studies, at higher levels of solar activity, have always been associated with challenges due to the limitations of numerical modulation models. We employ a three-dimensional numerical model based on stochastic differential equations and, owing to the numerical stability of this model, avoid such limitations at solar maximum conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The first robust observational evidence of charge-sign dependent solar modulation was reported in [138] and modelled in [139] using a drift model which, today, is known as a first generation drift model. These type of drift models predicted that during A > 0 polarity cycles the intensity ratio of negative to positively charged particles as a function of time should exhibit a ∧ shape profile while during A < 0 cycles it should exhibit a ∨ shape around minimum modulation periods, but when only the waviness of the HCS was changed with time [140]; for updates and new insights, see Figures 2 and 3 in [141]. It was found that when other modulation parameters were also changed with time in later generation drift models these distinctive shapes fade and are been smoothed out (e.g., [106]).…”
Section: Positron Modulationmentioning
confidence: 99%
“…The first robust observational evidence of charge-sign dependent solar modulation was reported in [138] and modelled in [139] using a drift model which, today, is known as a first generation drift model. These type of drift models predicted that during A > 0 polarity cycles the intensity ratio of negative to positively charged particles as a function of time should exhibit a ∧ shape profile while during A < 0 cycles it should exhibit a ∨ shape around minimum modulation periods, but when only the waviness of the HCS was changed with time [140]; for updates and new insights, see Figures 2 and 3 in [141]. It was found that when other modulation parameters were also changed with time in later generation drift models these distinctive shapes fade and are been smoothed out (e.g., [106]).…”
Section: Positron Modulationmentioning
confidence: 99%